Association between ultraprocessed foods consumption, eating disorders, food addiction and body image: a systematic review - Cintia Curioni; Thamíris Pereira; Michel Carlos Mocellin (BMJ Open)
Objective This study aimed to assess the association between ultraprocessed foods (UPF) consumption, eating disorders (EDs), food addiction and body image concerns.Design Systematic review following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines.Data sources Medline, Scopus, Web of Science, EMBASE, LILACS and APA PsycInfo databases, for studies published between 2009 and July 2024.Eligibility criteria We included cross-sectional and cohort studies involving individuals of all ages, evaluating the association between UPF consumption, classified by the ‘NOVA system’, EDs, food addiction and body image. No restrictions were placed on diagnostic criteria, age and gender. Studies that modelled UPF consumption as both an exposure and an outcome were included.Data extraction and synthesis Data extraction and quality assessment were performed by two independent reviewers. Methodological quality was assessed using the Joanna Briggs Institute critical appraisal checklist.Results We did not identify any longitudinal studies. Nine cross-sectional studies were included (n=54 367 participants). One study assessed EDs types, including restrictive, bulimic, binge eating and other (not otherwise specified); three studies examined body dissatisfaction, while five studies investigated food addiction. The consumption of UPF was significantly associated with bulimic, binge eating and other ED and food addiction. No significant associations were identified between restrictive ED and body dissatisfaction.Conclusion This systematic review highlights a significant gap in research on this topic. Although some associations have been found, the findings are limited to cross-sectional studies with methodological limitations. The lack of longitudinal studies emphasises the need for more rigorous research to accurately assess the direction of these relationships.PROSPERO registration number CRD42022365154.